HUBUNGAN TINGKAT PERILAKU PENGOBATAN DENGAN KADAR GLUKOSA DARAH PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS SUNGAI MESA BANJARMASIN - Novia Ariani; Aisya Novrida Putri; Riza Alfian; Maria Ulfah; Amaliyah Wahyuni; Erna Prihandiwati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Diabetes mellitus Type 2 (DMT2) is a chronic disease that, if left untreated, can lead to complications such as macrovascular and microvascular disorders. DM is an incurable disease. The management and treatment of type 2 diabetes mellitus aim to control blood glucose levels to prevent severe complications. The purpose of this study is to examine DMT2 patient’s treatment behavior, DMT2 patient’s fasting blood glucose level, and the relationship between treatment behavior levels and blood glucose levels in type 2 diabetes mellitus patients at the Sungai Mesa Health Center in Banjarmasin. This study uses a cross-sectional design with 41 samples of type 2 diabetes mellitus patients selected through consecutive sampling technique. The results of the study showed that the treatment behavior level was dominated by the contemplation level (48.8%). Fasting blood glucose levels were dominated by uncontrolled fasting blood glucose levels (95.1%). There was no significant relationship between treatment behavior levels and blood glucose levels, with a p-value from the Spearman correlation test of > 0.05 (0.527). The conclusion of this study is that treatment behavior levels are not a major factor in controlling blood glucose levels.